Burnout, ethical climate and work organization in covid-19 intensive care units: mixed method study - Ademir Jones Antunes Dorneles; Graziele de Lima Dalmolin; Edison Luiz Devos Barlem; Rosemary Silva da Silveira; Rafaela Andolhe; Silviamar Camponogara; Tânia Solange Bosi de Souza Magnago; Valdecir Zavarese da Costa (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the association between burnout and the perception of the ethical climate in nursing professionals in the covid-19 Intensive Care Unit and the relationship with the organization of work from the perspective of managers of these units. Methods: mixed method study conducted in three university hospitals in southern Brazil from December 2021 to March 2022. A cross-sectional study was developed with 110 nursing professionals, followed by an exploratory-descriptive study through semi-structured interviews with six managers. Descriptive and analytical statistics and discursive textual analysis were used. Results: the prevalence of burnout was 10% and the perception of negative ethical climate was 24.5%. The association between burnout and ethical climate revealed overload and fatigue during working hours, related to tension, fear, and stress that emerged from the consequences of the organization and relations of work in the covid-19 Intensive Care Unit. Conclusions: there was an association between burnout and ethical climate and elements of the work organization.